Effect of FAM196B in human lung adenocarcinoma - Feng, Yu (J Cancer, 2018)
Lung cancer is the leading cause of cancer-related mortality worldwide. The present study focused on the function of family with sequence similarity 196 member B (FAM196B) in lung adenocarcinoma (LUAD). We analyzed lung carcinoma patients' data from the Cancer Genome Atlas (TCGA), and verify the change of FAM196B expression in 30 LUAD tissues and matched adjacent non-tumor tissues (> 5 cm) by tissue microarray. To investigate the role of FAM196B in LUAD, we used lentivirus-mediated short hairpin RNA (shRNA) to knockdown FAM196B expression in human LUAD cell line A549 and H1299 and assessed it by RT-qPCR and western blot. Celigo Imaging Cytometry System, MTT assays and colony formation were conducted to evaluate cell proliferation. Cell apoptosis were assayed by Annexin V staining. We found that FAM196B was significantly upregulated (P=5.06E-06) in LUAD compared with adjacent non-tumor tissues. Cell proliferation was inhibited in FAM196B-silenced A549 and H1299 cells using Celigo Imaging Cytometry System, MTT assays and colony formation assays. Apoptosis rate was significantly increased in FAM196B-shRNA group than the control group. In conclusion, Knockdown of FAM196B can inhibit cell proliferation, cell colony formation capacity, and promote cell apoptosis in A549 and H1299 cell lines. FAM196B may be one novel potential targets for treating patients with LUAD.